Dynamic binding of the bacterial chaperone Trigger factor to translating ribosomes in Escherichia coli - Hävermark, Tora; Metelev, Mikhail; Lundin, Erik; Volkov, Ivan L; Johansson, Magnus (Uppsala University, 2024)
This repository contains all raw data, software tools for data analysis, and scripts for generating the figures and tables provided in the main text and supplementary information of the manuscript "Dynamic binding of the bacterial chaperone Trigger factor to translating ribosomes in Escherichia coli".

The bacterial chaperone Trigger factor (TF) binds to ribosome-nascent chain complexes (RNCs) and co-translationally aids the folding of proteins in bacteria. Here, we used single-particle tracking (SPT) to measure TF binding to translating ribosomes inside living Escherichia coli. TF displays distinct binding modes — longer (ca 1 s) and shorter (ca 50 ms) RNC bindings. We conclude that TF, on average, stays bound to the RNC for only a fraction of the translation cycle. Further, binding events are interrupted only by transient excursions to a freely diffusing state (ca 40 ms), suggesting a highly dynamic binding and unbinding cycle of TF in vivo. We also show that TF competes with SRP for RNC binding, and in doing so, tunes the binding selectivity of SRP.

The data and corresponding analyses have been divided into folders corresponding to different experimental conditions. Each experimental condition folder contains raw microscopy images ("RawData") with three phase contrast images ("A_Phase"), one brightfield image ("B_Bf"), and a stack of fluorescence images ("C_553", "C_546", or "C_638", depending on what laser was used). The "Tracking_EXP_YY_YYYY" folder contains single-particle tracking analysis of the corresponding raw data, and the "HMM_analysis" folder contains HMM-based diffusion analysis of the single-particle trajectories. The "Tools" folder contains all software for data analysis, and "Figures_and_tables_scripts" contains scripts for generating figures and tables.
Keywords: Systems biology; Medical and Health Sciences; Medicin och hälsovetenskap; Biological Sciences; Biologi